Menstrual cycle distribution of uterine natural killer cells is altered in heavy menstrual bleeding - Biswas Shivhare, Sourima; Bulmer, Judith N.; Innes, Barbara A.; Hapangama, Dharani K.; Lash, Gendie E. (Journal of reproductive immunology, 2015)
•Reduced numbers of uNK cells in late secretory endometrium of women with HMB.•uNK cells are phenotypically altered in endometrium of women with HMB.•Other leukocyte populations are not altered. Heavy menstrual bleeding (HMB) affects 30% of women of reproductive age and significantly interferes with quality of life. Altered endometrial vascular maturation has been reported in HMB and recurrent miscarriage, the latter associated with increased uterine natural killer (uNK) cell numbers. This study compared endometrial leukocyte populations in controls and women with HMB. Formalin-fixed paraffin-embedded endometrial biopsies from controls (without endometrial pathology) and HMB were immunostained for CD14 (macrophages), CD56 (uNK cells), CD83 (dendritic cells), FOXP3 (regulatory T cells/Tregs), CD3 and CD8 (T cells). Leukocyte numbers were analysed as a percentage of total stromal cells in five randomly selected fields of view in the stratum functionalis of each sample. In control women across the menstrual cycle, 2–8% of total stromal cells were CD3+ cells, 2–4% were CD8+ T cells and 6–8% were CD14+ macrophages. Compared with controls, CD3+ cells were reduced during the mid-secretory phase (4%, P<0.01) and increased in the late secretory phase (12%, P=0.01) in HMB. CD83+ dendritic cells and FOXP3+ Tregs were scarce throughout the menstrual cycle in both groups. In controls, 2% of stromal cells in proliferative endometrium were CD56+ uNK cells, increasing to 17% during the late secretory phase. In HMB, CD56+ uNK cells were increased in the proliferative (5%, P<0.01) and early secretory (4%, P<0.02) phases, but reduced (10%, P<0.01) in the late secretory phase. This study demonstrates dysregulation of uNK cells in HMB, the functional consequence of which may have an impact on endometrial vascular development and/or endometrial preparation for menstruation.